Ba1.63La7.39Si11N23Cl0.42:Ce3+ – A Nitridosilicate Chloride with a Zeolite‐Like Structure1. Issue 8 (20th April 2016) - Schultz, Peter; Durach, Dajana; Schnick, Wolfgang; Oeckler, Oliver
Abstract: The nitridosilicate chloride Ba1.63 La7.39 Si11 N23 Cl0.42 :Ce 3+ was synthesized by metathesis reaction starting from LaCl3, BaH2, CeF3 and the product of the ammonolysis of Si2 Cl6 . The title compound is stable towards air and moisture. Diffraction data of a microcrystal were recorded using microfocused synchrotron radiation. X‐ray spectroscopy confirms the chemical composition of the crystal. IR spectra corroborate absence of N–H bonds. The compound is homeotypic to Ba2 Nd7 Si11 N23 and crystallizes in space group Cmmm with a = 11.009(3), b = 23.243(8), c = 9.706(4) Å and Z = 4, R 1 (all) = 0.0174. According to bond valence sum calculations, some crystallographic positions show complete occupancy by Ba or La whereas others contain significant amounts of both elements. In contrast to the structure prototype Ba2 Nd7 Si11 N23, Ba1.63 La7.39 Si11 N23 Cl0.42 :Ce 3+ contains chloride ions in channels of the SiN4 tetrahedra network, hinting at various substitution possibilities of the complex zeolite‐like structure. Abstract :